PERAN KEPEMIMPINAN INSTRUKSIONAL DALAM PENGEMBANGAN KURIKULUM ADAPTIF DI PENDIDIKAN DASAR BERBASIS KEBUTUHAN ABAD 21 - Nur Efendi (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
This study aims to analyze the role of instructional leadership in developing an adaptive curriculum based on 21st-century needs at SD Islam Al-Badar. The study employs a qualitative approach with a case study design focusing on leadership practices, curriculum development impact, and implementation challenges. Data were collected through in-depth interviews, classroom observations, and curriculum document analysis. The findings reveal that instructional leadership is implemented through academic supervision, teacher guidance, and collaborative planning. The principal promotes the integration of critical thinking, creativity, communication, and collaboration into classroom practices. The impact is reflected in improved curriculum quality that is more flexible, contextual, and student-centered. Challenges include differences in teacher competence, limited resources, and resistance to change. Adaptive leadership addresses these barriers through continuous professional development and strengthened collaboration. The findings indicate that instructional leadership plays a significant role in enhancing adaptive curriculum development in primary education.